Hybrid Materials and Nanocomposites as Multifunctional Biomaterials - D. M. Follmann, Heveline; F. Naves, Alliny; A. Araujo, Rafael; Dubovoy, Viktor; Huang, Xiaoxi; Asefa, Tewodros; Silva, Rafael; N. Oliveira, Osvaldo (Current Pharmaceutical Design, 2017)
This review article provides an overview of hybrid and nanocomposite materials used as biomaterials in nanomedicine, focusing on applications in controlled drug delivery, tissue engineering, biosensors and theranostic systems. Special emphasis is placed on the importance of tuning the properties of nanocomposites, which can be achieved by choosing appropriate synthetic methods and seeking synergy among different types of materials, particularly exploiting their nanoscale nature. The challenges in fabrication for the nanocomposites are highlighted by classifying them as those comprising solely inorganic phases (inorganic/inorganic hybrids), organic phases (organic/organic hybrids) and both types of phases (organic/inorganic hybrids). A variety of examples are given for applications from the recent literature, from which one may infer that significant developments for effective use of hybrid materials require a delicate balance among structure, biocompatibility, and stability.
Keywords: nanocomposites